Le verre du VIIIe au XVIe siècle en Europe occidentale - Pactat, Inès; Munier, Claudine (Les Cahiers de la MSHE Ledoux, 2020)
The 8th international conference of the AFAV, held in Besançon in December 2016, brought together a large number of medieval glass specialists. Presented in these proceedings, the communications renew, thanks to an interdisciplinary approach, the studies carried out on a material, which interested the archaeologists as the historians, the archaeometrists, the glass-makers and the conservators. They offer an overview of our knowledge of the glass from the eighth-sixteenth centuries in Portugal, Italy, Slovenia and the Balkans, and more punctually in Swiss, German and French regions, without forgetting also the exchanges with the New World (Canada) at the end of the considered period.